De la movilización tradicional a las redes de presión transnacional: violencia antisindical y derechos humanos en Colombia - López Pacheco, Jairo Antonio; Hincapié Jiménez, Sandra (El Colegio de México A.C., 2015)
The paper analyzes the mobilization in defense of the human rights of unionized workers in Colombia during the process of signing and ratification of the Free Trade Agreement with the United States (2004-2011). Based on case studies, it seeks to explain how international pressure networks were activated as an effective alternative to the traditional mobilization of unions amidst the trade agreement negotiations. This led to material and symbolic effects that remain unfulfilled to date, despite the historical persistence of antiunion violence in Colombia.